2015
DOI: 10.1007/s00707-015-1416-1
|View full text |Cite
|
Sign up to set email alerts
|

On the connection between microstructure and surface roughness of brass sheets and their formability

Abstract: The aim of this work was the analysis of the relationships between material properties and forming limits of a sheet, caused by the strain localization in the groove. In particular, we aim at the replacement of a nonmeasurable inhomogeneity coefficient of the material, the value of which has to be taken a priori, by measurable coefficients. In the proposed model, it is assumed that the material heterogeneity is a result of surface roughness and presence of internal defects (voids). The value of inhomogeneity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…5). This dependence is nearly linear (R 2 > 0.91), which supports the work of Stachowicz [24]. In the case of Ra parameter measured along the rolling direction in the range of strain between 0 and 20 %, a fast increasing of its value is observed.…”
Section: Roughness Averagesupporting
confidence: 85%
“…5). This dependence is nearly linear (R 2 > 0.91), which supports the work of Stachowicz [24]. In the case of Ra parameter measured along the rolling direction in the range of strain between 0 and 20 %, a fast increasing of its value is observed.…”
Section: Roughness Averagesupporting
confidence: 85%
“…As we found, the determination coefficient R 2 between roughness parameters values and the strain value is higher than 0.9104. The linear character of this relation is confirmed by Stachowicz [26]. The increase in surface roughness of the sheet is the result of reorientation and fragmentation of the individual grains, mainly in the subsurface.…”
Section: Results and Discussion 41 Surface Roughnessmentioning
confidence: 57%
“…Moreover, most studies showed that roughness linearly increases with the applied strain. For example, Stachowicz (2016) explored the surface roughness of different brass sheets in uniaxial and biaxial tensile tests, and found linearity between the surface roughness increment and the effective strain. Most studies, however, reported that the roughness increment is not a linear function.…”
Section: Introductionmentioning
confidence: 99%